An urban form response to disaster vulnerability: Improving tsunami evacuation in Iquique, Chile. (September 2016) - León, Jorge; March, Alan
As urbanization gathers pace and climate change increases the number and magnitude of many natural hazards, cities are increasingly becoming hot spots for disasters. Although the role of appropriate urban forms in reducing disaster vulnerability has been recognized for some time, the majority of its potential remains focused on long-term mitigation efforts. In contrast, examination of the relationships with short-term disaster management activities such as response and immediate recovery has not been thoroughly conducted. This paper contributes to this shortfall by analysing a critical type of rapid onset disaster, a near-field tsunami, and the role of urban form in supporting the populations' core response activities of evacuation and sheltering. The Chilean city of Iquique (affected by a severe earthquake and minor tsunami in 2014) is examined using a mixed methods approach that provides the basis for proposed macro-scale and micro-scale changes in its urban form; these modifications, in turn, are assessed with geographic information system (GIS) and agent-based computer models. The results show important existing evacuation vulnerability throughout major areas of the city (as the result of interrelated critical conditions), which nonetheless could be significantly reduced by the changes proposed. Further steps in this iterative process, in turn, could lead to the development of evacuation-based urban design standards capable of being transferred to different tsunami-prone contexts around the world.